Using the flow path of pressure turbines to discharge idle flows - Genrih V. Orekhov; Mikhail K. Sklyadnev (Мелиорация и гидротехника)
Purpose: to consider possible options for discharging idle flows through the flow path of the turbine of a medium- or high-head hydroelectric power plant equipped with reaction turbines. Materials and methods. A hydroelectric power plant with a pressure of about 50 m, equipped with a radial-axial turbine, is adopted as the initial data. The turbine capacity in the nominal mode is about 30 MW. According to the working hypothesis, a counter-vortex damper of the flow kinetic energy is installed in the turbine runner chamber (the turbine runner is dismantled), which is designed to dampen excess energy in the area of the draft tube cone and bend, ensuring the hydraulic regime of the water flow into the lower pool is the same as during operation of the standard turbine runner. Results. A hydraulic calculation of two swirling flows, which create a standard guide vane and an additional fixed grid of blades installed coaxially to the guide vane in the turbine runner chamber, was performed. Both grids form a counter-vortex flow in the draft tube, providing energy dissipation due to the water viscous forces. In the course of the research, the calculated geometric characteristics of the swirler grids providing swirl were obtained: the angles of the inlet and outlet edges of the blades and their radii. When installing a counter-vortex damper in the runner chamber of the hydraulic turbine, the discharge flow at a pressure of H = 49.35 m will be Q = 63.3 m³/s, while the counter-vortex damper provides power dissipation of NКГ = 29688 kW. The absence of a counter-vortex damper leads to the fact that the pressure pulsations are 32 % of the operating head. Conclusions. The calculations show that passing a high energy intensity flow through the flow path of the turbine tract is possible. This is achieved by installing a counter-vortex damper of the kinetic energy of the flow in the runner chamber.